FOOD RESTRICTION AND SUCROSE SUPPLEMENTATION: METABOLIC EFFECTS IN AN EXPERIMENTAL RAT MODEL - Galhardi, Cristiano Machado; Medeiros, Rodolfo de Oliveira; Rodrigues, Dauane Cristina Orso Toscan; Avallone, Mara Flávia Mamédio; Carneiro, Dênnis Penna; Carneiro, Joice de Fátima Alvares Penna; Domingues, Pedro Henrique Lima; Feitosa, Geovanna de Castro; Golono, Paula Takano; Tauil, Raissa Bulaty; et al. (INTERFERENCE: A JOURNAL OF AUDIO CULTURE, 2025)
Background: Nutrition plays a crucial role in regulating energy metabolism, and both food restriction during critical stages of development and excessive sucrose intake are known to induce long-lasting metabolic changes. However, little is understood about the combined effects of early-life food restriction and sucrose supplementation on metabolic outcomes in adulthood. Objective: This study aimed to evaluate the impact of early-life food restriction and sucrose supplementation on body composition, biochemical profile, and hormones related to energy metabolism in adult rats. Methods: Male Wistar rats from the Central Animal Facility of UNESP - Botucatu Campus were subjected to early-life food restriction through reduced suckling and subsequently allocated into four groups: Control (C), Control + Sucrose (CS), Restriction (R), and Restriction + Sucrose (RS). Sucrose supplementation (10% solution) was provided for 120 days. At the end of the protocol, body composition, biochemical parameters (blood glucose, lipid profile, insulinemia), and hormones (leptin and insulin) were assessed. Data were analyzed using ANOVA followed by Tukey’s test (p < 0.05). Results: Early-life food restriction significantly reduced body weight, while sucrose supplementation promoted greater caloric intake and feeding efficiency. Rats supplemented with sucrose exhibited elevated fasting blood glucose, triglycerides, and total cholesterol, suggesting dysregulation of glucose and lipid metabolism. Furthermore, sucrose intake, particularly in previously restricted animals, was associated with increased hepatic enzymes (ALT, AST), reinforcing the liver’s central role in metabolic alterations. Evidence also pointed to mechanisms involving oxidative stress and low-grade inflammation, contributing to insulin resistance. Conclusions: The findings indicate that sucrose supplementation, especially when combined with early-life food restriction, exerts deleterious effects on metabolic homeostasis in adulthood. These results underscore the importance of nutrient quality, beyond caloric content, in shaping long-term metabolic health and highlight the need for further research on the mechanisms underlying diet-metabolism interactions.